Ultrasound power Doppler synovitis is associated with plasma IL-6 in established rheumatoid arthritis. (July 2016) - do Prado, Aline Defaveri; Bisi, Melissa Cláudia; Piovesan, Deise Marcela; Bredemeier, Markus; Batista, Talita Siara; Petersen, Laura; Bauer, Moises Evandro; da Silveira, Inês Guimarães; Mendonça, José Alexandre; Staub, Henrique Luiz
Highlights: Plasma IL-6 is associated with swollen joint count, but not tender joint count in established RA. Plasma IL-6 is associated with wrists US synovitis in established RA. Plasma IL-6 is associated with 10-joint power Doppler independently of DAS28 in established RA. Abstract: Background and objective: Cytokines have an important role in the pathogenesis of rheumatoid arthritis (RA). Although plasma levels of IL-6 have been related to musculoskeletal ultrasound (MSUS) synovitis in early DMARD-naïve RA, there are no similar studies in established disease. Methods: 64 RA patients treated with non-biological DMARDs and 30 healthy controls were included in this prospective cross-sectional study. A blood sample was taken before evaluation of disease activity (DAS28) and ultrasonography (all tests performed in a blinded fashion). MSUS was performed by one of two ultrasound-trained rheumatologists on 10 joints of both hands. Gray scale (GS) and pD (power Doppler) synovitis were evaluated using a semi-quantitative scale (0–3) in individual joints, and their sum (score 10) was calculated. Plasma cytokines (IL-2, IL-4, IL-6, IL-10, IL-17, TNF, IFN-γ, and VEGF) were quantified by flow cytometry. Results: Levels of all cytokines, excepting VEGF, were significantly higher in RA patients than in controls (P ⩽ 0.05). In RA patients, IL-6, but not other cytokines, correlated positively with DAS28 and swollen joint count (P ⩽ 0.01), as well as with 10-joint pD score, and GS and pD of both wrists (P < 0.01 for all tests). In multiple linear regression, the association of IL-6 with 10-joint pD score was maintained even after adjustment for DAS28. However, there was no correlation of IL-6 with tender joint count, 10-joint GS score, or presence of erosions. Conclusion: We demonstrated an association of inflammatory findings on MSUS and plasma IL-6 independently of DAS28 in established RA.